ANALISIS YURIDIS TERHADAP KORBAN KEKERASAN SEKSUAL DI LINGKUNGAN KELUARGA MENURUT PERSPEKTIF UNDANG-UNDANG NOMOR 23 TAHUN 2002 JUNCTO UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK JUNCTO UNDANG-UNDANG NOMOR 12 TAHUN 2022 TENTANG TINDAK PIDAN - Zuraidah Zuraidah; Chaidar Awaludin Anwar (Universitas Majalengka, 2023)
With the existence of laws and regulations regarding sexual violence against children, Indonesia will be able to overcome all problems regarding children, especially sexual violence. The purpose of this research is to analyze the extent of the law in the application of protection and recovery for children who are in conflict with the law, in this case, sexual violence committed by relatives and their own family, and the factors that influence it. This research is normative (doctrinal) research. The results of this study indicate that in the legal analysis of child protection in the urgency of the child as a gift in the family, all efforts are made to create conditions so that every child can exercise his rights and obligations and encourage normal development and growth of children physically, mentally and socially. Furthermore, the results of the research show that the main factors in the recovery of the child are law enforcement, the condition of the child, government facilities in handling post-violence recovery, and the last one in the family as the main actor. Therefore, the role of the government should be more embracing children who are victims of their own family's disrepute.